PENGGUNAAN PARTIKEL NANKA DAN NANTE DALAM KOMIK HANAZAKARINO KIMITACHI E KARYA NAKAJOU HISAYA - Wawondatu, Yunita (Humanis; Volume 5. No. 3. Desember 2013, 2013)
Nanka & nante particles are one of toritatejoshi. Hanazakarino Kimitachi e comic is one of the Japanese literature work in which there are matters relating to Nanka and Nante particle. By using the theory of Horin, the Hanazakarino Kimitachi e comic is examined from the point of view of Japanese particles to see the meanings of nanka & nante. Methods and techniques that are used in this research are descriptive methods and interpretation technique. The results showed that based on their uses, there are seven particles structure of nanka and nante, and there are four categories of nanka and nante besed on meaning. In this case some of the data found substusional relation between nanka and nante.
Keywords: Nanka, Nante, Semantic